Bis(mu-diphenylarsine-kappa As-2:As)bis[tetracarbonyltungsten(0)] - Tiekink, E.R.T.; Wardell, J.L. (International Union of Crystallography, 2010)
The title compound, [W-2(C12H10As)(2)(CO)(8)], features a diamond-shaped W2As2 core with a W-W distance of 3.0948 (7) angstrom. The coordination geometry for each W atom is based on a pentagonal bipyramid within a As2C4W donor set, with carbonyl ligands defining the axial positions; the As atoms exist within distorted tetrahedral C2W2 donor sets.